Biology and exploitation of the blue swimmer crab, Portunus pelagicus - A.P., Dineshbabu (Indian Journal of Fisheries, 2011)
Portunus pelagicus Â 2 test) obtained for the years 1998-2005 was 1:1. Peak spawning activity occurred during February-March. Size at maturity (50%) of females was estimated at 96 mm carapace width. Growth was isometric and males were heavier than females of similar size. By von Bertalanffy’s growth plot, it was estimated that males and females reach 123 and 128 mm (CW) respectively at the end of one year and reach 156 and 160 mm respectively in two years. Longevity of P. pelagicus is estimated as 3 years in both sexes. The total mortality coefficient (Z), natural mortality coefficient (M) and fishing mortality coefficient (F) values estimated for the species were 6.3, 2.2 and 4.1 respectively. The exploitation ratio (E) was 0.65 and L c was estimated at 87.7 mm. MSY was estimated as 367 t against the present annual average yield of 333 t. From ’Thompson and Bell yield prediction analysis it is seen that any additional 10% effort from the present level will yield only less than 10% additional catch, indicating that increasing the effort will not be economical. Restricting the catch to MSY level (367 t) is suggested as a suitable management option for the sustainability of P. pelagicus fishery from the coast. supports indigenous as well as mechanised fishery of Karnataka coast. Trawlers accounted for 98% of the landing and the highest landing was observed during 2001-2002 (403 t). The peak fishing season for crabs was during December-June. Size range observed in the fishery was 56 to 165 mm in males and 61 to 170 mm in females. The homogeneity of sex ratio (